1984
DOI: 10.1007/bf00422578
|View full text |Cite
|
Sign up to set email alerts
|

The influence of extra load on the mechanical behavior of skeletal muscle

Abstract: Eleven international jumpers and throwers engaged in year round training were divided into experimental (n = 6) and control (n = 5) groups. The experimental group was tested before and after a 3 weeks simulated hypergravity period, and again 4 weeks after the hypergravity period. The high gravity condition was created by wearing a vest weighing about 13% of the subjects body weight. The vest was worn from morning to evening including the training sessions, and only removed during sleep. The daily training of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
4

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 20 publications
3
19
0
4
Order By: Relevance
“…On top of that, exposure to vibration for a long time span can be harmful as it causes disease and muscular-skeletal pain [1][2][3]. Therefore, there are need for vibration control with the adequate approaches in order to avert all these awful effects.…”
Section: Introductionmentioning
confidence: 99%
“…On top of that, exposure to vibration for a long time span can be harmful as it causes disease and muscular-skeletal pain [1][2][3]. Therefore, there are need for vibration control with the adequate approaches in order to avert all these awful effects.…”
Section: Introductionmentioning
confidence: 99%
“…Possible mechanisms for documented responses include, but are not limited to, the tonic vibration reflex, [6][7][8][9][10] angiogenic factors (outgrowth of new capillaries from preexisting vessels) such as matrix metalloproteinases and vascular endothelial growth factor, [11][12][13][14] testosterone and growth hormone, 15 and activation of stem cells. 16 To date, most literature 7,[17][18][19] regarding muscular performance has focused on the lower extremity, with minimal work exploring the upper extremity. Although authors 18,20,21 have examined the characteristics associated with individual finger, wrist, and elbow flexors, none have tested the rotator cuff using WBV.…”
mentioning
confidence: 99%
“…It may be concluded that the higher load caused an increased nerve pulsing to the periphery, in order to maintain the movement intensity, resulted in stride reduction, thereby increasing the stride frequency. The adaptation of the body in mentioned circumstances is of neurogenic and myogenic nature (Bosco, Zanon, Rusko, Dalmonte, Bellotti, Latteri et al, 1984;Milner-Brown et al, 1975;Moritan & De Vries, 1979;Thornton & Rummel, 1974; according to Bosco et al, 1986; 1 Russo & Bosco, 1987) and it is carried out by a relatively quick adaptation of neural factors by increasing the number of recruited motor units, the increased level of discharge and their better mutual work synchronization. However, the second phase (of myogenic adaptation), is characterized by the increase of their glycolytic potential and lasts for several months (McDonagh & Davies, 1984; according to Bosco et al, 1984), which justly points to the need of a special study of experimental treatment duration and possibly leads to doubt regarding the length of the treatment applied in this study given the different plasticity of some tested variables.…”
Section: Results and Discusionmentioning
confidence: 99%